KOHESI REFERENSI TEKS ARAB - Muhammad Ridwan (Arabic Literature Department, 2015)
This research will elaborate the reference of cohesion in the Arabic language. This research is using the discourse of muqaddimah (introduction) of Al-Munjid Dictionary first edition, written by Louis Ma’luf Al-Yasui as the source of data. The methods that had been used in this research were distributively method – distribusionalism using the technique of directly substances divided, the technique of reading the marks, the technique of change, and the technique of paraphrase. In the muqaddimah of Al-Munjid dictionary discourse, first edition, written by Louis Ma’luf Al-Yasui, the result of analysis can be concluded that there are two kinds of reference cohesion, (1) based on the substances that has been refered, such as endophora (anaphora and cataphora) and exophora, (2) based on the type of reference, such as reference of persona and reference of demonstrative.